Developing an ICT-Integrated Differentiated Learning Model to Address the Diverse Learning Styles of Islamic Religious Education Students - Wardatul Baidho; Zakiyah BZ (At-tadzkir: Islamic Education Journal, 2026)
The diversity of learning styles among students of Islamic Religious Education (PAI) at Nurul Jadid University has not been fully accommodated through uniform instructional approaches, thus necessitating the development of a more adaptive instructional model integrated with digital technology. This study aims to develop an ICT-based differentiated learning model capable of systematically and contextually addressing the diversity of students’ learning styles. This research employs a qualitative case study design. Data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that the use of ICT in the learning process remains general and has not been consistently implemented in line with differentiation principles, resulting in suboptimal learning experiences. Thematic analysis identifies four major needs: the diversity of students’ learning styles, the need to adjust instructional strategies, students’ instructional needs, and the demand for more flexible learning. Based on these findings, an ICT-based differentiated learning model is formulated, consisting of learning style identification, differentiation design, multi-path learning implementation, and adaptive evaluation. The findings further indicate that the proposed model can serve as a strategic alternative to enhance the quality of learning in higher education. Its implementation can encourage lecturers to adopt more adaptive teaching practices and improve student engagement, motivation, and learning effectiveness, particularly in Islamic Religious Education programs.